2017
DOI: 10.1002/adhm.201700695
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold‐Based microRNA Therapies in Regenerative Medicine and Cancer

Abstract: The field of "regenerative medicine" (RM) was conceptually developed to aid the body's natural capacity to self-repair, a capacity which is impaired with age and in cases of disease or injury. [1] RM is a vast and multifaceted area of medicine, often microRNA-based therapies are an advantageous strategy with applications in both regenerative medicine (RM) and cancer treatments. microRNAs (miRNAs) are an evolutionary conserved class of small RNA molecules that modulate up to one third of the human nonprotein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 195 publications
(223 reference statements)
0
52
0
Order By: Relevance
“…The use of RNA‐based therapeutics eliminates the requirement for nuclear entry, often regarded to be the rate‐limiting step in the delivery of pDNA‐based therapeutics, as the plasmid must enter the nucleus to gain access to the machinery required for transcription . RNA‐based therapeutics offer several exciting approaches to gene therapy as RNA molecules such as messenger (m)RNA, small interfering RNA (si)RNA, short hairpin (sh)RNA, and micro (mi)RNA are involved throughout the transcriptional, regulatory and other functional activities of the cell.…”
Section: Gene‐activated Scaffolds For Orthopedic Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of RNA‐based therapeutics eliminates the requirement for nuclear entry, often regarded to be the rate‐limiting step in the delivery of pDNA‐based therapeutics, as the plasmid must enter the nucleus to gain access to the machinery required for transcription . RNA‐based therapeutics offer several exciting approaches to gene therapy as RNA molecules such as messenger (m)RNA, small interfering RNA (si)RNA, short hairpin (sh)RNA, and micro (mi)RNA are involved throughout the transcriptional, regulatory and other functional activities of the cell.…”
Section: Gene‐activated Scaffolds For Orthopedic Tissue Engineeringmentioning
confidence: 99%
“…The ability to silence specific genes represents a promising therapeutic approach for various orthopedic disorders . A comprehensive review of scaffold‐based miRNA delivery in regenerative medicine was recently published by our lab . Here, in addition to highlighting scaffold‐based miRNA delivery, we also review some exciting scaffold‐based delivery approaches using siRNA for the regeneration of cartilage.…”
Section: Gene‐activated Scaffolds For Orthopedic Tissue Engineeringmentioning
confidence: 99%
“…Many scaffolds have been designed to fulfill the function of miRNA delivery, mainly hydrogels, nanofibers, and porous or spongy scaffolds. Besides, the normal desired properties such as biocompatibility, easy fabrication, easy sterilization, proper mechanical properties, and adequate porosity for vessels growth, the material must retain the miRNA complexes while facilitating their sufficient exposure to the infiltrating cells without affecting its mechanical properties [68].…”
Section: Influence Of Vascularization On Scaffold Design For Osteochomentioning
confidence: 99%
“…PRP in particular may represent a valuable option for knee OA treatment, but the number of randomized controlled studies remains limited and the use of standard preparations is lacking. Importantly, growth factor therapy has been questioned due to the need for high dosages, that not only leads to high production costs, but also increases the risk of side effects . This can be caused by the exposure of joint tissues other than cartilage (synovium, tendons, ligaments, meniscus, subchondral bone) to the exogenous growth factors leading to synovial hyperplasia, joint inflammation and ectopic cartilage or bone formation, with pain and loss of mobility due to joint obstruction .…”
Section: Overview Of Anti‐chondrogenic Regulatorsmentioning
confidence: 99%
“…Importantly, growth factor therapy has been questioned due to the need for high dosages, that not only leads to high production costs, but also increases the risk of side effects. 14 This can be caused by the exposure of joint tissues other than cartilage (synovium, tendons, ligaments, meniscus, subchondral bone) to the exogenous growth factors leading to synovial hyperplasia, joint inflammation and ectopic cartilage or bone formation, with pain and loss of mobility due to joint obstruction. 15 Several studies have confirmed that repeated injections of TGF-b, Andrea BMP2, or BMP9 and adenoviral overexpression of TGF-b in murine knee joints can cause the formation of osteophytes.…”
mentioning
confidence: 99%